ARSENIC POLLUTION FROM PHOSPHOGYPSUM PRODUCED AT MULTAN, PAKISTAN - Javied, S.; Chaudhary, M. M.; Irfan, N.; Tufail, M.; Siddique, N.; Waheed, S. (The Nucleus, 2020)
Phosphogypsum (PG) is a by–product of the phosphate fertilizer industry, which contains various toxic elements. The concentration of one of the toxic elements, arsenic, has been measured in 10 samples of PG waste collected from the stack of the Pak-Arab Fertilizer factory at Multan in Pakistan. The technique of instrumental neutron activation analysis (INAA) was employed for the characterization of this element. The quality assurance was controlled by analyzing the reference materials, IAEA-SL1, IAEA-SDM-2 and GSJ-JB-2 along with the PG samples. The concentration of arsenic was found to vary from 1.55 to 11.39 µg/g with an average value of 6.26 µg/g. The level of arsenic in the PG samples was compared with the permissible value of this element in soil and water. The potential hazard of this element to human health and the environment has been discussed and method to control this pollution has been proposed in this paper.